The Effect of Organizational Commitment, Job Placement Suitability, and Leadership Style on Employee Performance in UMKM Kasongan Tourism Village, Special Region of Yogyakarta - Nanik Istiroah; Sundjoto Sundjoto; Sri Rahayu; Christina Wulansari (Universitas Alma Ata, 2024)
Using a by-order system in making pottery in UMKM Kasongan Tourism Village has resulted in many craftsmen feeling less able to develop their abilities which affects performance. This study aims to test organizational commitment, suitability of job placement, and leadership style on employee performance. The population of this study was all workers as craftsmen in Kasongan Tourism Village, totaling 43 employees who as craftsmen data came from Kasongan Village. The sampling technique used saturated samples. The analysis tool for this study used multiple linear regression which was processed using SMART PLS. The results of the study said that organizational commitment did not affect employee performance, while suitability of job placement and leadership style had a positive and significant effect on employee performance. The implications of this study say that in developing human resources in craftsmen, leadership style and suitability of job placement are needed to improve employee performance.